2015
DOI: 10.1186/s12886-015-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular foreign bodies extracted by pars plana vitrectomy: clinical characteristics, management, outcomes and prognostic factors

Abstract: BackgroundIntraocular foreign bodies (IOFBs) are an important cause of visual loss within the group of working age population. We aim to present the clinical features and the algorithm according to which we manage the foreign bodies that are located in the posterior segment of the eye. We define the outcomes and the prognostic factors that influenced the final visual acuity and globe survival in patients with IOFBs that we extracted by pars plana vitrectomy (PPV) over a 5-year period.MethodsWe reviewed the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 25 publications
8
53
2
3
Order By: Relevance
“…The majority of patients were working adults (84.7%) and males (97.2%), and similar findings are found world-wide in studies of ocular trauma 1,[9][10][11][12] . The time lapse between injury and admission to hospital varied from 1 to 10 days, however this parameter alone did not affect the final visual acuity.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The majority of patients were working adults (84.7%) and males (97.2%), and similar findings are found world-wide in studies of ocular trauma 1,[9][10][11][12] . The time lapse between injury and admission to hospital varied from 1 to 10 days, however this parameter alone did not affect the final visual acuity.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with retinal detachment at presentation, had a significantly lower postoperative BCVA. This was confirmed in the study of Lin et al 13 and Nicoara et al 10 , although other authors found no correlation 1,8 . The occurrence of retinal detachment was not affected by the time lapse between the injury and admission, localization of the wound, size or localization of IOFB, presence of iris injury or endophthalmitis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Posterior segment metallic intraocular foreign bodies (IOFBs) are one of leading causes of visual morbidity and blindness, especially among the young and middleaged working populations [1,2]. They present very distinct surgical challenges since these objects travel at high speeds serially through the ocular organs, moving from the cornea into the lens and, vitreous cavity and finally impacting the retina.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in microsurgical vitreoretinal surgery techniques and instrumentation has allowed managing successfully traumatized eyes with IOFBs [7, 8]. In very few reports 25-gauge vitrectomy surgery was successfully used for the removal of foreign bodies and to manage ocular lesions using different maneuvers [911]. In this case series we report our experience in treating open eye injuries with IOFBs by 25-gauge pars plana vitrectomy in order to evaluate the final visual acuity, globe survival, and complication rate and to describe the proceedings of IOFBs removal and the management of ocular lesions correlated.…”
Section: Introductionmentioning
confidence: 99%